Metal free acid base catalyst in the selective synthesis of 2,5-diformylfuran from hydroxynnethylfurfural, fructose, and glucose - Rathod, P. V.; Nale, S. D.; Jadhav, V. H. (ACS Sustainable Chemistry & Engineering, 2017)
A novel metal free acid-base (CC-SO3H-NH2) catalyst was synthesized by introducing acidic -SO3H, -COOH, and silyloxypropylamine (-OSiCH2CH2CH2NH2) functional groups on glucose derived carbocatalyst. The catalyst was characterized by Fourier transform infrared (FTIR), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) analyses. Superior catalytic activity was shown by the catalyst toward one-pot synthesis of DFF using molecular oxygen as the sole oxidant. The catalyst was found to be highly selective in synthesis of 2,5-diformylfuran (DFF) from hydroxymethylfurfural (HMF), fructose, and, more importantly, from glucose with excellent yields. Moreover, the catalyst was easily recycled and reused without any significant loss in its catalytic activity.